Prevention programs and prenatal diagnosis for beta thalassemia in Pakistan: a narrative review - Mahmood Ghafoor; Muhammad Farooq Sabar; Furqan Sabir (Journal of the Pakistan Medical Association, 2020)
Beta thalassemia in Pakistan is a serious health concern with an estimated 5-8% carrier frequency and birth of 5000 major children every year in the country. The treatment of beta thalassemia major patients poses a great economic burden; hence, the ideal approach towards this disease should encompass effective prevention services. At present only one government funded project “Punjab Thalassemia Prevention Program” existed in Punjab province, and providing free of cost services for beta thalassemia screening and prenatal diagnosis. Complete blood count and hemoglobin electrophoresis remains the preliminary test for screening, while chorionic villi sampling and amplification refractory mutation system method have been most widely used for molecular diagnosis of beta thalassemia. Modern molecular techniques, non-invasive prenatal diagnosis, and pre-implantation diagnosis are in trial phases. In this review we have discussed the available diagnostic facilities and status of prevention programs for beta thalassemia in Pakistan as well as future perspectives.Continuous..